Phosphoric Acid Industry Problems and Solutions - Schorr Wiener, Michael; Valdez, Benjamin (IntechOpen, 2017)
Phosphoric acid is an important industrial acid that is utilized for manufacturing phosphatic fertilizers and industrial products, for pickling and posterior treatment of steel surfaces to prevent corrosion, for ensuring appropriate paint adhesion, and for the food and beverages industry, e.g., cola-type drinks to impart taste and slight acidity and to avoid iron sedimentation. This industry is spread out in countries of four continents - Asia, Africa, America, and Europe - which operate mines and production plants and produce fertilizers. Phosacid is one of the most widely known acids. The global phosacid market and its many phosphate derivatives are expanding worldwide; this trend is expected to continue in the next years, thus producing innovative products.